Perencanaan hutan kota sebagai pengendali kenyamanan termal (studi kasus: Subak Munduk Gendang, Desa Kesiman Kertalangu, Kecamatan Denpasar Timur, Kota Denpasar, Bali) - Restyatama, I Made Dwita Hadi; Asmiwyati, I Gusti Agung Ayu Rai; Gunadi, I Gusti Alit (Jurnal Arsitektur Lansekap; Vol.6, No.2, Oktober 2020, 2020)
Urban forest planning as a thermal comfort controller (case study: Subak Munduk Gendang, Kesiman Kertalangu village, East Denpasar district, Denpasar City, Bali). Urban Forest is a land stretching with dense trees growing in urban areas both on state land and public land, in which is appointed as urban forest by government official authority. One function of the urban forest is to ameliorate microclimate in urban areas so that thermal comfort will increase. The aim of this research is to design urban forest as controller of thermal comfort. This research uses the potential analysis method, site constraints method, amenity method, danger signal method, Thermal Humidity Index (THI), vegetation analysis methods, and linear regression methods. The site of this research is divided into three zone, such as extensive zone, semi intensive zone and intensive zone based on the potential and the constraint of biophysical aspects of the site. The result of this research is on the plan of adding tree green space about 20,53% or 15610 m2 of the total area of Subak Munduk Gendang, thereby it is estimated that THI value <27,00 (ideal THI 27,00).